Microwave static calcination for removal of high chlorine from hot-dip galvanizing ash for preparing ceramic glaze-grade zinc oxide - Fan, Yuteng; Liu, Sihao; Luo, Yongguang; Sun , Hongyan (Archives of Metallurgy and Materials, 2026)
Microwave static calcination for removal of high chlorine from hot-dip galvanizing ash for preparing ceramic glaze-grade zinc oxide